Preparation method of nanoparticle reinforced magnesium-based material intermediate alloy
By performing surface modification and dispersion of nanoparticles, combined with low melting point metals and ultrasonic technology, the problems of low elastic modulus of magnesium alloys and easy agglomeration of nanoparticles are solved, and efficient dispersion and performance improvement of magnesium-based materials are achieved.
Patent Information
- Application Number
- CN202411409554.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The elastic modulus of magnesium alloys is low, which leads to the need to increase volume in component design to improve stiffness, thereby weakening its lightweight advantage. The nano-strengthening phase is prone to agglomeration and difficult to disperse at high temperatures, affecting its comprehensive utilization efficiency.
The nanoparticles are surface modified to form an oleophilic hydrophobic film layer and dispersed into low-melting metals, combined with ultrasonic and high shear mixing techniques to form an intermediate alloy, followed by rapid cooling and extrusion treatment in a magnesium-based material , improve the dispersion ability and yield of nanoparticles.
It effectively improves the dispersion ability and yield of the nano-strengthening phase, avoids surface modification failure at high temperatures, enhances the elastic modulus of magnesium-based materials, and improves the overall performance of the material.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a nano-particle reinforced magnesium-based material master alloy, and belongs to the field of industrial magnesium alloys. Background Art
[0002] As the lightest metal structural material, magnesium alloy has important potential application value in the fields of aerospace and weapon equipment. In recent years, its application has been gradually increasing, making it an important alternative material for structural weight reduction.
[0003] Although magnesium alloys have significant advantages, their intrinsic properties have restricted the expansion of their applications. The most prominent one is the low elastic modulus of magnesium alloys. In the design process of components, it is often necessary to increase the volume to achieve an increase in stiffness, which weakens the lightweight advantage of magnesium alloys. Therefore, the development of high modulus magnesium alloy systems and related preparation and processing methods will be one of the effective ways to promote the in-depth development of magnesium materials.
[0004] Adding reinforcements is an effective means to improve the elastic modulus of magnesium alloys. The methods of adding reinforcements include external addition and endogenous methods, among which external reinforcements are the mainstream method of magnesium-based composite materials. As an excellent reinforcement phase, nano-reinforced phase can enhance the elastic modulus of alloys. However, the nano-reinforced phase has an extremely high specific surface energy. Under the interaction of van der Waals forces and electrostatic forces, it is very easy to agglomerate, and there is a lack of effective industrial dispersion methods. Therefore, how to avoid the segregation of nano-reinforced phases has become the focus of current work. In addition, in addition to being easy to agglomerate itself, the nano-reinforced phase also has the problem of a large diameter difference with the matrix. Nanoparticles are very easy to segregate in the gaps between the matrix, and they also have the natural problem of being difficult to disperse.
[0005] Therefore, exploring methods to effectively disperse nanoparticles and improve their comprehensive utilization efficiency is a key problem that needs to be overcome urgently. Adding intermediate alloys can effectively increase the yield of valuable substances, especially for second phases or solute elements that are difficult to decompose. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a nanoparticle-reinforced magnesium-based material master alloy, which improves the dispersion ability of the reinforcement phase and further improves the yield of the nano-reinforcement phase by prefabricating the master alloy.
[0007] To achieve the above object, the present invention adopts the following technical solutions: A method for preparing a nanoparticle-reinforced magnesium-based material master alloy comprises the following steps: (1) Surface modification of nanoparticles to form an oleophilic and hydrophobic surface film layer; (2) dispersing the surface-modified nanoparticles into a low-melting-point metal to form a mixture; (3) Dispersing the mixture to obtain a nanosuspension, then adding micrometer-sized pure magnesium powder to the nanosuspension, and stirring while adding with the aid of ultrasonic waves until no obvious liquid is left; (4) cutting a circular hole in a pure magnesium ingot, rapidly cooling the resulting mixture into a solid, then placing the solid into the circular hole in the magnesium ingot, and sealing the circular hole with a magnesium plug; (5) The pure magnesium ingot is sealed into an iron crucible, placed in an induction heating furnace for heating, and the temperature is rapidly raised to 690-710°C at a rate of 25°C / min, and kept at this temperature for 30-60min. The crucible is then placed in a high-energy vibration device to assist electromagnetic stirring; (6) Rapidly water-cooling the sealed iron crucible and cutting to obtain a nano-granular magnesium ingot; (7) The nanoparticle magnesium ingot is heated to between 250 and 350° C., kept warm for 1 to 2 hours, and extruded after being heated to a uniform temperature. The extrusion ratio is controlled between 20 and 25 to obtain a deformed nanoparticle-reinforced magnesium-based material intermediate alloy.
[0008] Preferably, the nanoparticles are one or more of SiO2, TiC, TiB2, and SiC. The size of the nanoparticles is D50=5-30 nm. The surface of the nanoparticles is modified by esterification, surface grafting reaction, or coupling agent.
[0009] Preferably, in step (2), the low melting point metal is one or more of Ga, In, Hg and Sn. The low melting point metal is melted into a liquid state, and then 3-10% of the surface-modified nanoparticles are added by volume to form a mixture.
[0010] Preferably, in step (3), the mixture is firstly subjected to ultrasonic dispersion and then dispersed in a high shear mixer, and the ultrasonic dispersion time is controlled within 20 to 30 minutes.
[0011] Preferably, in step (4), the diameter of the circular hole is 30-50 mm.
[0012] Beneficial effects of the present invention: 1. Since nanoparticles have an extremely high specific surface area, surface modification can be used to achieve deagglomeration and improve the dispersion ability of the particles.
[0013] 2. Since the surface modification film layer of nanoparticles is mostly organic, it will carbonize or fail at high temperatures. Therefore, low-melting-point metals are introduced as auxiliary dispersants during the preparation of intermediate alloys. On the one hand, it can prevent the aggregation of particles, and at the same time, it can avoid the failure of surface modification caused by high temperature problems. The most important thing is that these low-melting-point metals can also be used as components of magnesium alloys in subsequent use.
[0014] 3. By adding micron-sized magnesium powder during the auxiliary dispersion process, the liquid metal can be better dispersed into the magnesium powder, and it can also play an isolation role to form a local closed loop.
[0015] 4. Applying ultrasonic stirring and high shear mixer to liquid metal in sequence can further achieve deagglomeration and accelerate the dispersion of nanoparticles.
[0016] 5. Extruding the master alloy can further improve the element recovery rate of the master alloy as an auxiliary additive. DETAILED DESCRIPTION
[0017] The present invention is further described below in conjunction with the embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.
[0018] The specific scheme of the method for preparing the nanoparticle phase reinforced magnesium-based material master alloy provided by the present invention comprises the following steps: (1) Select one or more of nano-scale SiO2, TiC, TiB2, and SiC, control the particle size between 5 and 30 nm, and modify the particle surface by esterification, surface grafting reaction, or coupling agent to form an oleophilic and hydrophobic surface film.
[0019] (2) Dispersing the surface-modified nanoparticles into a low-melting-point metal, which includes one or more of the metals Ga, In, Hg and Sn, melting the metal into a liquid state, and then adding 3 to 10% of the surface-modified nanoparticles to form a mixture.
[0020] (3) The mixture is placed in an ultrasonic field to accelerate the dispersion of the nanoparticles in the mixture. The dispersion time is controlled at 20 to 30 minutes. The particles are then placed in a high shear mixer to further reduce the specific surface energy, accelerate the dispersion of the particles, and construct a nanosuspension. Then, micron-level pure magnesium powder is added to the suspension and stirred while adding it with the assistance of ultrasound until no obvious liquid is left.
[0021] (4) A circular hole with a diameter of 30-50 mm is cut in the pure magnesium ingot, and the nanosuspension + magnesium powder mixture is quickly cooled into a solid. The solid is then placed into the pre-prepared circular hole of the magnesium ingot, ensuring that the mixture does not liquefy during the whole process. The circular hole on the pure magnesium ingot is then sealed with a magnesium plug.
[0022] (5) The pure magnesium ingot is sealed into an iron crucible, placed in an induction heating furnace for heating, and the temperature is rapidly raised to 690-710°C at a rate of 25°C / min, and kept warm for 30-60 min. The crucible is then placed in a high-energy vibration device to assist electromagnetic stirring, accelerate the movement of the melt, and achieve rapid dispersion of the nanoparticles therein.
[0023] (6) The sealed iron crucible is quickly water-cooled to prevent the sedimentation of the nanoparticles, and a magnesium + nanoparticle ingot with good surface quality is obtained after cutting.
[0024] (7) The magnesium + nanoparticle ingot is heated to between 250 and 350° C., kept warm for 1 to 2 hours, and then extruded after being uniformly heated. The extrusion ratio is controlled between 20 and 25 to obtain a modified magnesium + nanoparticle intermediate alloy.
[0025] Example 1 Select 20nm SiO2 nanoparticles and use acetone to clean them to remove surface impurities and organic pollutants. Disperse the cleaned SiO2 nanoparticles in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, heat it under nitrogen protection. After reacting for 24 hours, use ethanol to remove the unreacted silane coupling agent and by-products to obtain SiO2 particles with an oleophilic and hydrophobic surface film. Use water bath heating to melt the metal Ga into a liquid state, and then add 5% of surface-modified SiO2 nanoparticles to form a mixture. Put the mixture into an ultrasonic field for ultrasonic dispersion treatment, and the dispersion time is 22 minutes. The dispersed particles are continued to be placed in a high shear mixer, the speed is selected to be 2000 r / min, the treatment time is 1 hour, and a nano suspension is constructed. Then add micron-level pure magnesium powder to the suspension, and use auxiliary ultrasonic waves to stir while adding until there is no obvious liquid. A circular hole with a diameter of 40 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0026] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 705°C at a rate of 25°C / min, kept warm for 55 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 25°C, a magnesium + SiO2 nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + SiO2 nanoparticle ingot was heated to 330°C, kept warm for 2 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 22, to obtain a deformed magnesium + SiO2 nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the SiO2 particles was about 26 nm after statistics. After ICP testing, the yield of SiO2 nanoparticles was calculated to be about 91%.
[0027] Example 2 Select 10 nm SiC nanoparticles and use acetone to clean them to remove surface impurities and organic pollutants. Disperse the cleaned SiC nanoparticles in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, heat it under nitrogen protection. After reacting for 20 h, use ethanol to remove the unreacted silane coupling agent and by-products to obtain SiC nanoparticles with an oleophilic and hydrophobic surface film. Use water bath heating to melt the metal In into a liquid state, and then add 10% of surface-modified SiC nanoparticles to form a mixture. Put the mixture into an ultrasonic field for ultrasonic dispersion treatment for 25 min. Put the dispersed particles into a high shear mixer again, select a speed of 2200 r / min, and treat for 1.5 h to construct a nano suspension. Then add micron-level pure magnesium powder to the suspension, and use auxiliary ultrasonic waves to stir while adding until there is no obvious liquid. A circular hole with a diameter of 35 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0028] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 710℃ at a rate of 25℃ / min, kept warm for 40 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 20℃, a magnesium + SiC nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + SiC nanoparticle ingot was heated to 340℃, kept warm for 2 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 25, to obtain a deformed magnesium + SiC nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the SiC particles was about 16 nm after statistics. After ICP testing, the yield of SiC nanoparticles was calculated to be about 90%.
[0029] Example 3 Select 15 nm TiC nanoparticles and use acetone to clean them to remove surface impurities and organic pollutants. Disperse the cleaned TiC nanoparticles in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, heat it under nitrogen protection. After reacting for 24 hours, use ethanol to remove the unreacted silane coupling agent and by-products to obtain TiC nanoparticles with an oleophilic and hydrophobic surface film. Use water bath heating to melt the metal Ga into a liquid state, and then add 5% of surface-modified TiC nanoparticles to form a mixture. Put the mixture into an ultrasonic field for ultrasonic dispersion treatment for 30 min. The dispersed particles are continued to be placed in a high shear mixer, the speed is selected to be 1900 r / min, the treatment time is 2 h, and a nano suspension is constructed. Then, micron-level pure magnesium powder is added to the suspension, and auxiliary ultrasonic waves are used to stir while adding until there is no obvious liquid. A circular hole with a diameter of 50 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0030] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 690°C at a rate of 25°C / min, kept warm for 30 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 23°C, a magnesium + TiC nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + TiC nanoparticle ingot was heated to 300°C, kept warm for 1.5 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 20, to obtain a deformed magnesium + TiC nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the TiC particles was about 21 nm after statistics. After ICP testing, the yield of TiC nanoparticles was calculated to be about 88%.
[0031] Example 4 Two nanoparticles of TiC and SiC with a size of 20 nm were selected and cleaned with acetone to remove impurities and organic pollutants on the surface. The cleaned TiC and SiC nanoparticles were dispersed in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, it was heated under nitrogen protection. After 18 hours of reaction, ethanol was used to remove the unreacted silane coupling agent and by-products to obtain TiC and SiC nanoparticles with oleophilic and hydrophobic surface films. The metal In was melted into a liquid state by heating in a water bath, and then 10% of the surface-modified TiC and SiC nanoparticles were added to form a mixture. The mixture was placed in an ultrasonic field for ultrasonic dispersion treatment for 30 min. The dispersed particles were continued to be placed in a high shear mixer, the speed was selected to be 2500 r / min, the treatment time was 1 h, and a nano suspension was constructed. Then, micron-level pure magnesium powder was added to the suspension, and auxiliary ultrasonic waves were used to stir while adding until there was no obvious liquid. A circular hole with a diameter of 45 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0032] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 700℃ at a rate of 25℃ / min, kept warm for 40 min, and then placed in a high-energy vibration device with auxiliary electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 25℃, magnesium + TiC and SiC nanoparticle ingots with good surface quality were obtained by cutting. Finally, the magnesium + TiC and SiC nanoparticle ingots were heated to 320℃, kept warm for 1 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 24, to obtain a modified intermediate alloy of magnesium + TiC and SiC nanoparticles. The prepared alloy was observed by TEM, and it was found that the average diameter of TiC and SiC nanoparticles was about 26 nm after statistics. After ICP testing, the yield of TiC and SiC nanoparticles was calculated to be about 92%.
[0033] Example 5 30nm SiO2 nanoparticles were selected and cleaned with acetone to remove surface impurities and organic pollutants. The cleaned SiO2 nanoparticles were dispersed in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, it was heated under nitrogen protection. After 18 hours of reaction, ethanol was used to remove the unreacted silane coupling agent and by-products to obtain SiO2 nanoparticles with an oleophilic and hydrophobic surface film. The metal Sn was melted into a liquid state by heating in a water bath, and then 10% of the surface-modified SiO2 nanoparticles were added to form a mixture. The mixture was placed in an ultrasonic field for ultrasonic dispersion treatment for 30 min. The dispersed particles were continued to be placed in a high shear mixer, the speed was selected to be 2200 r / min, the treatment time was 1.2 h, and a nano suspension was constructed. Then, micron-level pure magnesium powder was added to the suspension, and auxiliary ultrasonic waves were used to stir while adding until there was no obvious liquid. A circular hole with a diameter of 45 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0034] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 700℃ at a rate of 25℃ / min, kept warm for 50 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 25℃, a magnesium + SiO2 nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + SiO2 nanoparticle ingot was heated to 280℃, kept warm for 1 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 25, to obtain a modified magnesium + SiO2 nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the SiO2 particles was about 34 nm after statistics. After ICP testing, it was calculated that the yield of SiO2 nanoparticles was about 90%.
[0035] Example 6 Select 10 nm TiB2 nanoparticles and use acetone to clean them to remove surface impurities and organic pollutants. Disperse the cleaned nano-TiB2 in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, heat it under nitrogen protection. After reacting for 24 hours, use ethanol to remove the unreacted silane coupling agent and by-products to obtain nano-TiB2 particles with an oleophilic and hydrophobic surface film. Use water bath heating to melt the metal In into a liquid state, and then add 8% of surface-modified TiB2 nanoparticles to form a mixture. Put the mixture into an ultrasonic field for ultrasonic dispersion treatment for 25 min. Put the dispersed particles into a high shear mixer again, select a speed of 1800 r / min, and treat for 2 h to construct a nano suspension. Then add micron-level pure magnesium powder to the suspension, and use auxiliary ultrasonic waves to stir while adding until there is no obvious liquid. A circular hole with a diameter of 40 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0036] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 710℃ at a rate of 25℃ / min, kept warm for 60 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 25℃, a magnesium + TiB2 nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + TiB2 nanoparticle ingot was heated to 350℃, kept warm for 1 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 20, to obtain a deformed magnesium + TiB2 nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the TiB2 particles was about 17 nm after statistics. After ICP testing, it was calculated that the yield of TiB2 nanoparticles was about 90%.
[0037] Example 7 Select 25 nm SiC nanoparticles and use acetone to clean them to remove surface impurities and organic pollutants. Disperse the cleaned nano-SiC in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, heat it under nitrogen protection. After 18 hours of reaction, use ethanol to remove the unreacted silane coupling agent and by-products to obtain SiC nanoparticles with an oleophilic and hydrophobic surface film. Use water bath heating to melt the metal Sn into a liquid state, and then add 10% of surface-modified SiC nanoparticles to form a mixture. Put the mixture into an ultrasonic field for ultrasonic dispersion treatment for 20 min. The dispersed particles are continued to be placed in a high shear mixer, the speed is selected to be 2000r / min, the treatment time is 1.5 h, and a nano suspension is constructed. Then, micron-level pure magnesium powder is added to the suspension, and auxiliary ultrasonic waves are used to stir while adding until there is no obvious liquid. A circular hole with a diameter of 40 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0038] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 700°C at a rate of 25°C / min, kept warm for 55 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 25°C, a magnesium + SiC nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + SiC nanoparticle ingot was heated to 290°C, kept warm for 1.5 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 25, to obtain a deformed magnesium + SiC nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the SiC particles was about 30nm after statistics. After ICP testing, the yield of SiC nanoparticles was calculated to be about 87%.
[0039] Example 8 20 nm TiC, SiO2 and SiC nanoparticles were selected and cleaned with acetone to remove surface impurities and organic pollutants. The cleaned TiC, SiO2 and SiC nanoparticles were dispersed in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, it was heated under nitrogen protection. After 20 h of reaction, ethanol was used to remove the unreacted silane coupling agent and by-products to obtain TiC, SiO2 and SiC nanoparticles with oleophilic and hydrophobic surface films. The metal Sn was melted into a liquid state by heating in a water bath, and then 5% of the surface-modified TiC, SiO2 and SiC nanoparticles were added to form a mixture. The mixture was placed in an ultrasonic field for ultrasonic dispersion treatment for 25 min. The dispersed particles were continued to be placed in a high shear mixer, the speed was selected to be 2300 r / min, and the treatment time was 1.5 h to construct a nano suspension. Then, micron-level pure magnesium powder was added to the suspension, and auxiliary ultrasonic waves were used to stir while adding until there was no obvious liquid. A circular hole with a diameter of 50 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0040] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 710℃ at a rate of 25℃ / min, kept warm for 60 min, and then placed in a high-energy vibration device with auxiliary electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 25℃, magnesium + TiC, SiO2 and SiC nanoparticle ingots with good surface quality were obtained by cutting. Finally, the magnesium + TiC, SiO2 and SiC nanoparticle ingots were heated to 250℃, kept warm for 2 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 25, to obtain a modified intermediate alloy of magnesium + TiC, SiO2 and SiC nanoparticles. The prepared alloy was observed by TEM, and it was found that the average diameter of TiC, SiO2 and SiC particles was about 26 nm after statistics. After ICP testing, the yield of TiC, SiO2 and SiC nanoparticles was calculated to be about 91%.
[0041] Example 9 30 nm TiB2 nanoparticles were selected and cleaned with acetone to remove surface impurities and organic pollutants. The cleaned TiB2 nanoparticles were dispersed in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, it was heated under nitrogen protection. After reacting for 24 h, ethanol was used to remove the unreacted silane coupling agent and by-products to obtain TiB2 nanoparticles with an oleophilic and hydrophobic surface film. The metal Hg was melted into a liquid state by heating in a water bath, and then 5% of the surface-modified TiB2 nanoparticles were added to form a mixture. The mixture was placed in an ultrasonic field for ultrasonic dispersion treatment for 20 min. The dispersed particles were continued to be placed in a high shear mixer, the speed was selected to be 2500 r / min, the treatment time was 0.5 h, and a nano suspension was constructed. Then, micron-level pure magnesium powder was added to the suspension, and auxiliary ultrasonic waves were used to stir while adding until there was no obvious liquid. A circular hole with a diameter of 40 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0042] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 710℃ at a rate of 25℃ / min, kept warm for 30 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 20℃, a magnesium + TiB2 nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + TiB2 nanoparticle ingot was heated to 330℃, kept warm for 1 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 21, to obtain a deformed magnesium + TiB2 nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the TiB2 particles was about 36nm after statistics. After ICP testing, it was calculated that the yield of TiB2 nanoparticles was about 90%.
[0043] Example 10 Select 15 nm SiC nanoparticles and clean them with acetone to remove surface impurities and organic pollutants. Disperse the cleaned nano-SiC in isopropanol to form a uniform suspension. After adding an appropriate amount of silane coupling agent to the suspension, heat it under nitrogen protection. After reacting for 24 hours, use ethanol to remove the unreacted silane coupling agent and by-products to obtain SiC nanoparticles with an oleophilic and hydrophobic surface film. Use water bath heating to melt the GaIn alloy into a liquid state, and then add 8% of surface-modified SiC nanoparticles to form a mixture. Put the mixture into an ultrasonic field for ultrasonic dispersion treatment for 30 min. Put the dispersed particles into a high shear mixer again, select a speed of 1800 r / min, and treat for 2 h to construct a nano suspension. Then add micron-level pure magnesium powder to the suspension, and use auxiliary ultrasonic waves to stir while adding until there is no obvious liquid. A circular hole with a diameter of 50 mm was cut in the pure magnesium ingot, and the mixture of nanosuspension and magnesium powder was quickly cooled into a solid. The solid was then placed in the circular hole of the magnesium ingot prepared in advance. The mixture was ensured not to liquefy during the whole process. The circular hole on the pure magnesium ingot was then sealed with a magnesium plug.
[0044] The above pure magnesium ingot was sealed into an iron crucible, placed in an induction heating furnace for heating, and quickly heated to 710°C at a rate of 25°C / min, kept warm for 40 min, and then the crucible was placed in a high-energy vibration device and assisted by electromagnetic stirring. After the sealed iron crucible was quickly water-cooled to 20°C, a magnesium + SiC nanoparticle ingot with good surface quality was obtained by cutting. Finally, the magnesium + SiC nanoparticle ingot was heated to 350°C, kept warm for 1 h, and extruded after being heated to a uniform temperature, with an extrusion ratio of 20, to obtain a modified magnesium + SiC nanoparticle intermediate alloy. The prepared alloy was observed by TEM, and it was found that the average diameter of the SiC particles was about 21nm after statistics. After ICP testing, the yield of SiC nanoparticles was calculated to be about 91%.
Claims
1. A method for preparing a nanoparticle-reinforced magnesium-based master alloy, characterized in that: The following steps are involved: (1) Surface modification of nanoparticles to form an oleophilic and hydrophobic surface film layer; (2) dispersing the surface-modified nanoparticles into a low-melting-point metal to form a mixture; (3) Dispersing the mixture to obtain a nanosuspension, then adding micrometer-sized pure magnesium powder to the nanosuspension, and stirring while adding with the aid of ultrasonic waves until no obvious liquid is left; (4) cutting a circular hole in a pure magnesium ingot, rapidly cooling the resulting mixture into a solid, then placing the solid into the circular hole in the magnesium ingot, and sealing the circular hole with a magnesium plug; (5) The pure magnesium ingot is sealed into an iron crucible, placed in an induction heating furnace for heating, and the temperature is rapidly raised to 690-710°C at a rate of 25°C / min, and kept at this temperature for 30-60min. The crucible is then placed in a high-energy vibration device to assist electromagnetic stirring; (6) Rapidly water-cooling the sealed iron crucible and cutting to obtain a nano-granular magnesium ingot; (7) The nanoparticle magnesium ingot is heated to between 250 and 350° C., kept warm for 1 to 2 hours, and extruded after being heated to a uniform temperature. The extrusion ratio is controlled between 20 and 25 to obtain a deformed nanoparticle-reinforced magnesium-based material intermediate alloy.
2. The method for preparing a nanoparticle-reinforced magnesium-based master alloy according to claim 1, characterized in that: The nanoparticles are one or more of SiO2, TiC, TiB2, and SiC.
3. The method for preparing the nanoparticle-reinforced magnesium-based master alloy according to claim 2, characterized in that: The size of the nanoparticles is D50=5~30nm.
4. The method for preparing a nanoparticle-reinforced magnesium-based master alloy according to claim 1, characterized in that: The surface of the nanoparticles is modified by esterification, surface grafting reaction or coupling agent method.
5. The method for preparing a nanoparticle-reinforced magnesium-based master alloy according to claim 1, characterized in that: The low melting point metal is one or more of Ga, In, Hg and Sn.
6. The method for preparing a nanoparticle-reinforced magnesium-based master alloy according to claim 1, characterized in that: In the step (2), the low melting point metal is melted into a liquid state, and then 3 to 10% by volume of the surface-modified nanoparticles are added and dispersed to form a mixture.
7. The method for preparing a nanoparticle-reinforced magnesium-based master alloy according to claim 1, characterized in that: In the step (3), the mixture is firstly subjected to ultrasonic dispersion and then dispersed in a high shear mixer, and the ultrasonic dispersion time is controlled within 20 to 30 minutes.
8. The method for preparing a nanoparticle-reinforced magnesium-based master alloy according to claim 1, characterized in that: In step (4), the diameter of the circular hole is 30-50 mm.
Citation Information
Patent Citations
Method of preparing cemented carbide or cermet alloy
CA2041668A1
Carbon nano-reinforced aluminum-based conductor material and preparation method
CN110760720A
Nano-diamond reinforced biological magnesium alloy and preparation method thereof
CN113732311A
Magnesium nanoparticle coated graphene reinforced magnesium-based composite material with excellent interface bonding characteristic and preparation method of magnesium nanoparticle coated graphene reinforced magnesium-based composite material
CN116144967A
Low-cost low-density high-modulus magnesium alloy and preparation method thereof
CN117265352A